Virtual reality for learning mathematics: a systematics literature review - Dewi, Niken Shofiana; Juandi, Dadang; Hoq, S M Afzal; Hendriyanto, Agus (AIP Publishing, 2024)
The use of virtual reality (VR) in learning is a manifestation of the rapid development of science and technology today. Even so, there are still not many studies that comprehensively discuss the use of VR in learning mathematics. This research aims to analyze studies related to this topic from 2018 to 2022 using the PRISMA protocol. Article searches in the Scopus and ERIC databases yielded 13 articles. Next, it will be divided into five themes: mathematical learning outcome types, VR types, research subject, research approach, VR role in affecting mathematics learning, and main topics in mathematics using VR-based learning. The results of this systematic literature review are expected to help develop further research by paying attention to important things that need to be improved when using VR while learning mathematics.